Frequency of Re-Fracture in Osteoporotic Patients - Asad Hanif, Asif Ali Shaikh, Muhammad Rafique Jakhrani, Rasheed Ahmed Bhatti, Fahad Noor Memon, Waliullah Qureshi, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the frequency of re-fracture in osteoporotic patients presenting @ SMBBMU Larkana Subject and Methods: This is Descriptive Cross-sectional study, accompanied at Department of Orthopedics, SMBBMU and Civil hospital Karachi, for period of 6 months from 19-07-2018 to 19-01-2019. Total of 130 osteoporotic patients with previous fracture were included in this study. Brief histories for the duration of present complain and history of previous fracture was taken. Presence of pain, tenderness and mobility at the site of trauma was noted. X rays Anterio-posterior/Lateral of the effected site was done and presence of fracture with break in the continuity of the bone was considered as re-fracture. Data was collected on structured proforma. Results: A total of 130 osteoporotic patients with previous fracture were selected in our study. The average age of the patients was 58.77±4.27 years. Average duration of presenting complains and previous fractures were 3.93 ± 0.87 days and 7.11±1.23 months. There were 1:1 male to female ratio. Out of 130 patients, 68.46% were type II diabetic, 83.85% were hypertension. Frequency of re-fracture in osteoporotic patients was observed in 8.46% (11/130) Conclusion: Fracture is common presentation in osteoporotic bones. Our study showed that rates of re-fracture range up to 8.46% in patients with an initial osteoporotic fracture, depending on the type of initial fracture. Keywords: Osteoporosis, Osteoporotic fractures, fracture and Re-fracture.